A rapid assessment of the impact of coronavirus disease (COVID- 19) pandemic on health care & service delivery for noncommunicable diseases in India. Issue 10 (October 2022) - Nath, Anita; Sudarshan, Kondalli Lakshminarayana; Rajput, Gurpreet Kaur; Mathew, Stany; Chandrika, Karur Raghavendra Rao; Mathur, Prashant
Abstract: Background and aim: The coronavirus disease (COVID-19) pandemic had disrupted the availability, access and utilisation of routine health care services. The present study aimed to assess the impact of COVID-19 pandemic restrictions on India's Non communicable Disease (NCD) health care service delivery. Methods: The study included existing hospitals in disease registry network of the Indian Council of Medical Research-National Centre for Disease Informatics and Research (ICMR-NCDIR), Bengaluru. The study participants comprised site investigators who were clinicians from many specialities, including general medicine, surgery, cancer, neurology, cardiology, and endocrinology. A standardised questionnaire was prepared to collect data on NCD health care services at the respective hospitals over three months from March to May 2020. Results: Out of 153 hospitals approached for the study, 106 (70%) agreed to participate. Of these, 16 hospitals fully converted for COVID-19 care were excluded from the study. Thus, data from 90 hospitals were included in the final analysis. There had been a total disruption of NCD-related healthcare services during the three months in 44% of the hospitals. In April 2020, the outpatient attendance for over one-third of the hospitals was reduced by more than 75%. Admissions for planned surgeries for cancer treatment were reduced by more than 75% for about 40% of the hospitals. Preventive activities and population-based screening for diabetes, hypertension and cancer appear to have been adversely affected, with about one-third of the hospitals reporting total disruption in April and May 2020. As many as 60% of the institutions reported adequate availability of doctors. Over 91% of the institutions had preparedness/action plans to ensure the continuity of NCD services. Conclusion: The study shows that despite adequate human and material resources, NCD outpatient services, elective surgeries and population-based screening were severely affected. Most institutions were prepared to overcome the pandemic-imposed disruption and ensure a continuum of care for NCDs'. Highlights: The COVID 19 pandemic had imposed a considerable disruption on NCD related health services in India. Outpatient services, hospital admissions, elective surgeries and cancer screening activities were primarily affected. Health care facilities must formulate effective NCD continuum of care protocols during pandemics.